Real Time Trans-Rectal Elastography of Prostate Correlation with Histopathology in a Suspected Case of Prostate Cancer - Basnet, B.; Suwal, S.; Chataut, D.; Lohani, B.; Paudel, S. (Kathmandu University Medical Journal, 2021)
Background Early detection of prostate cancer, the second most common cancer in men worldwide, is the key for its successful treatment. Commonly used clinical criteria and imaging tools for detection of prostate cancer are less sensitive. Objective This study was aimed to find role of real time transrectal elastography of prostate for detection of prostate cancer. Method Study was conducted in 66 patients with clinical suspicion of prostate cancer, who were sent for ultrasound guided prostate biopsy. Transrectal ultrasound with real time elastography was performed in all the patients prior to the biopsy and looked for hard areas within the prostate. Then six-core tru-cut biopsy were taken in six zones of prostate, including the hard areas detected in the elastography. The histopathology report were correlated with the elastography findings. Result Median prostate specific antigen of the patients was 11.5 ng/ml with interquartile range of 8 to 23.5 ng/ml. Digital rectal examination showed hard nodular findings in 35 patients. Transrectal ultrasound showed 81 hypoechoic lesions in 31 patients. Elastography showed 127 hard areas in 31 patients. Histopathology showed 90 positive biopsy cores in 23 patients. Cancer detection rate of elastography was 82.6%. At 95% confidence interval, patients with elastography detected hard lesions had 19.4 times more likelihood to have prostate cancer. Sensitivity of elastography was high as compared to digital rectal examination and transrectal ultrasound alone. Conclusion Transrectal elastography had high sensitivity over clinical tools and transrectal ultrasonography for detection of prostate cancer.